Evaluating the Incidence and Risk Factors for Acute Cellular Rejection in a Steroid Sparing Liver Transplant Center. Issue 5 (May 2023) - Zhang, Xunjie; Lichvar, Alicia; Chan, Christine; Choi, David
Background: Corticosteroids has been the mainstay of immunosuppression (IMS) following liver transplant (LT). With the advent of more potent IMS, complete steroid withdrawal has become possible after LT. However, there is limited data regarding the incidence and risk factors for acute cellular rejection (ACR) in LT recipients on steroid sparing regimens. Objective: To identify the incidence and risk factors of ACR in LT recipients at an urban LT center utilizing a steroid-sparing IMS regimen. Methods: This was a single center retrospective study evaluating incidence of ACR in adults (>18 years) who received a LT between 01/01/2008 and 6/30/2019 at a steroid-sparing liver transplant center. Data between patients who had ACR and patients who did not were compared and risk factors were identified by multivariate logistic linear regression. Results: A total of 266 patients were included in this analysis, of which 18.4% experienced ACR within the first year of LT. Median time to first ACR was 134 (interquartile range [IQR]: 34-246) days. Black race (odds ratio [OR]: 4.39, P < 0.001), continued need for prednisone (OR: 2.80, P = 0.015) and cytomegalovirus (CMV) viremia (OR: 6.27, P < 0.001)) were independent risk factors for ACR. Tacrolimus use was associated with less ACR (OR: 0.33, P = 0.013). Conclusion and Relevance: Steroid sparing regimens for IMS post-LT were not associated with an increased incidence of ACR when compared to reported ACR rates in literature. Potential risk factors for ACR include Black race, the use of prednisone maintenance IMS therapy, and CMV viremia.